Peran Guru Dalam Meningkatkan Karakter Siswa Melalui Pembelajaran Pendidikan Pancasila di SMA Negeri 2 Sungai Pinang - Rotari, Septi; Mita Purnama; Nanang Jayani; Citra Lidiawati; Rike Erlande; Ideham Syahzili (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The purpose of this research is to determine the role of teachers in improving student character through learning Pancasila education at SMA Negeri 1 Sungai Pinang. This research uses descriptive qualitative methods. Data collection techniques using interviews, observation and documentation. The results of research on the role of teachers in improving student character through learning Pancasila education at SMA Negeri 1 Sungai Pinang. It was found that teachers have a very important role in growing and developing the character of each student. This can be seen from the Pancasila education subject, the teacher invites students to pray before starting the lesson and also pray after finishing the lesson, the teacher invites each student to practice the Pancasila values, one of which is the value of religious character and discipline character through material on the Pancasila education subject, the control card. , and congregational prayers. Keywords: Role of Teachers; Character Education; Pancasila Education.